Minority Television Trade as Cultural Journey: The Case of New Zealand’s Bro’Town - Havens, Timothy (Watching While Black, 2012)
Four animated, brown-skinned youth are lounging on a porch step in Auckland, New Zealand, when a fierce-looking social worker and police constable approach and insist on knowing where the father of two of the boys is. As the constable raises his nightstick, one of the boys fumbles in heavily accented Māori English, “He went to the pub four days ago and hasn’t been back.” The authorities quickly cart two of the boys off as wards of the state as another performs a Māori haka, or war chant, in mock warning to the police.
Keywords: 1-TV; 2-Approches sociologiques; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); Nouvelle-Zélande/Aotearoa (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Indigenous Feature Film Production in Canada: A National and International Perspective - Goulet, Danis; Swanson, Kerry (ImagineNATIVE Film + Media Arts Festival, 2014)
The goal of this research is to examine Aboriginal feature film production in Canada, specifically within the genre of drama. This report documents the rise of Indigenous cinema worldwide and examines Canada's public funding landscape including funding allocations to Aboriginal feature film production from Canada's public funders of film over a five-year period from 2007 to 2012. This report also examines the barriers to feature film production for Aboriginal content creators in Canada, and suggests areas of opportunity that can be targeted in order to boost production in this sector. Aboriginal film production is a relatively young sector, with scarce research existing on the industry. To address this gap in the available information on the sector, the researchers expanded the scope of the study beyond public funding agencies in Canada to include data from public funding agencies in Australia and New Zealand. Aboriginal feature film production in Canada is situated within a global Indigenous cinema context. Australia and New Zealand, in particular, are two pillars of global Indigenous film that offer a realistic point from which to compare Canada's progress. As a result, data from Australia and New Zealand are included in the study, as well as one model in the United States.
Keywords: 1-Cinéma; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Video Games Around the World - Wolf, Mark J. P. (MIT Press, 2015)
Video games have become a global industry, and their history spans dozens of national industries where foreign imports compete with domestic productions, legitimate industry contends with piracy, and national identity faces the global marketplace. This volume describes video game history and culture across every continent, with essays covering areas as disparate and far-flung as Argentina and Thailand, Hungary and Indonesia, Iran and Ireland.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé